The Communicative Language Teaching and Students’ Vocabulary Memorizing Improvement - Onco Rumbouw (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2021)
CLT is one of the techniques used to improve students' ability to learn vocabulary. Apart from memorizing vocabulary, students are also expected to be able to use vocabulary to communicate with one another, both indoors and outdoors. The type of research used by researchers is library research. This study aims to determine the development of learning using the CLT technique on vocabulary which was carried out in previous years, from 2008 to 2019. The samples taken were five articles, namely two published journal articles, two regular articles that were unpublished and one thesis. as well as researchers using qualitative methods to analyze some of these articles. The type of data used by researchers is document data. Following the data and results analyzed by the researcher, it can be said that learning using the CLT technique on vocabulary is not effective if it only relies on vocabulary without combining all the skills (Listening, Reading, Writing and Speaking) that exist in language learning. Therefore, if teachers want CLT learning to Vocabulary to be effective, then all the skills in the language must be combined so that the achievement of the desired results can be realized.